Uji Efektivitas Pupuk NPK (20-51-13) terhadap Pertumbuhan dan Produksi Tanaman Kubis melalui Foliar Spray - Hafith Furqoni (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
Fertilization is one of the important activities in plant cultivation because it plays a role in increasing productivity by maintaining soil fertility. This experiment aimed to test the effectiveness of NPK fertilizer (20-51-13) on the growth and production of cabbage plants and its agronomic effectiveness. The experimental design used was a randomized block design. The treatments tested: without application of the tested fertilizer (P0), application of inorganic fertilizer comparison (2 kg/ha/application) (P1), and 5 levels of NPK fertilizer (20-51-13) tested, namely: 1.0, 1.5, 2.0, 2.5, and 3.0 kg/ha/application. The recommended doses of urea, SP-36, and KCl fertilizers were  200, 100, and 100 kg/ha, respectively. The results showed that the application of NPK fertilizer (20-51-13) can increase the growth of cabbage plants as indicated by the variables of plant height and number of cabbage leaves compared to the control treatment. In addition, the application of NPK fertilizer (20-51-13) increased the yield components of cabbage plants compared to the control treatment. The treatment of 0.75 doses of NPK fertilizer (20-51-13) was agronomically effective because it produced the highest relative agronomic effectiveness value of 145%, which means it can increase yields by 1.45 times. The recommended dose for cabbage plants is 1.5 kg/ha/application of NPK fertilizer (20-51-13) applied 5 times at 2, 3, 4, 5, and 6 WAP.